Основные результаты комплексных исследований ЮгНИРО в Азово-Черноморском бассейне и Мировом океане - Gubanov, E.P.; Southern Scientific Research Institute of Marine Fisheries and Oceanography (YugNIRO) (YugNIRO, 1998)
The results of YugNIRO complex studies concerning the state of marine ecosystems, resources, the level of fish productivity of water bodies and prospects in utilization of living resources in the Azov and Black Seas and in some areas of the Indian Ocean promising for the Ukrainian fisheries were represented. The assessment of anthropogenic impact on biocenoses and populations of dominant target species was given. The specific features in application of artificial reefs-biofilters in the Sea of Azov and problems in sturgeon farming development were reviewed. Представлены результаты комплексных исследований ЮгНИРО состояния морских экосистем, сырьевой базы, уровня промысловой продуктивности водоемов и перспективы использования живых ресурсов Азово-Черноморского бассейна и некоторых районов Индийского океана, перспективных для рыболовного флота Украины. Дана оценка антропогенного влияния на биоценозы и популяции основных промысловых объектов. Рассмотрены особенности применения искусственных рифов-биофильтраторов в Азовском море и проблемы развития осетроводства. Published